Substituent constants (σp−) of the rotated nitro group : the interplay between the substituent effect of a rotated −NO2 group and H-bonds affecting π-electron delocalization in 4-nitrophenol and 4-Nitrophenolate complexes : a B3LYP/6-311+G** study - Dobrowolski, Michal A. (Array, 2009)
The geometries of a series of nine 4-substituted nitrophenols and 4-substituted nitrophenolates (X = H, CONH2, CHO, COOH, COCH3, COCl, CN, NO2, NO) and of their conformers, where the nitro group rotates by 10º from φ = 0° to φ = 90°, were optimized at the B3LYP/6-311+G** DFT level. These data were used to analyse the effect of rotating of the nitro group on π-electron delocalization in the ring. It has been shown that the substituent effect stabilization energy (SESE) estimated for p-substituted phenolates correlates very well with σp− constants. Based on this dependence the σp− constants for the nitro group as a function of the out-of-plane dihedral angle φ were obtained. Application of the model simulating varying strength of H-bond by approaching F− (HF) group to OH (O−) group of the 4-nitrophenol (4-nitrophenolate) with the rotating nitro group allowed to show interrelation between changes in aromaticity of the ring due to both rotation of the nitro group and changes in the strength of H-bonding.